2021
DOI: 10.5209/reve.75561
|View full text |Cite
|
Sign up to set email alerts
|

Emprendimiento digital femenino para el desarrollo social y económico: características y barreras en España

Abstract: El presente estudio centra su atención en un tipo particular de emprendimiento: el emprendimiento digital iniciado por mujeres. Este tipo de creación de empresas tiene un interés particular por su alto impacto en el desarrollo económico y la dinamización de las economías desarrolladas; y en muchos casos además por su intensa orientación social. Aquí resulta especialmente relevante encontrar una paridad entre hombres y mujeres a la hora de emprender, ya que, de lo contrario, no se obtendría un desarrollo inclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
2
1
1
Order By: Relevance
“…The study reveals significant gender differences in certain aspects of digital entrepreneurship competences, with women scoring higher on achievement orientation and men scoring higher on initiative. Results that do not coincide exactly with those obtained in the study by Tejeiro et al (2021), which highlighted parity between men and women regarding entrepreneurship. Although similar results are not obtained with the study of Vall-Llosera et al (2022), which concluded that athletic men who combine studies with paid work have more developed entrepreneurial competence.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The study reveals significant gender differences in certain aspects of digital entrepreneurship competences, with women scoring higher on achievement orientation and men scoring higher on initiative. Results that do not coincide exactly with those obtained in the study by Tejeiro et al (2021), which highlighted parity between men and women regarding entrepreneurship. Although similar results are not obtained with the study of Vall-Llosera et al (2022), which concluded that athletic men who combine studies with paid work have more developed entrepreneurial competence.…”
Section: Discussioncontrasting
confidence: 88%
“…Studies carried out on the development of entrepreneurial ability in higher education students indicate that the profile of students who present greater entrepreneurial competence is that of an athletic man who combines studies with paid work and who accesses university studies through the itinerary of Vocational Training (Vall-Llosera, Repart, Saurina & Serra, 2022). However, another study conducted by Tejeiro, Molina and García (2021) indicates that it is especially relevant to find parity between men and women when it comes to entrepreneurship, since otherwise, inclusive development would not be achieved, nor would all the entrepreneurial potential of a society be exploited.…”
Section: State Of the Art: The Competence Of Digital Entrepreneurship...mentioning
confidence: 99%
“…Similarly, Kolle et al (2021) affirm that female digital entrepreneurship has an impact on economic development, which dynamizes the economy, and that the main difficulty faced by digital entrepreneurs is related to finding financing. In the case of women, another barrier is the role of women in their families.…”
Section: Perspectives On Digital Entrepreneurshipmentioning
confidence: 94%
“…La falta de referentes puede llevar a la creencia de que el emprendimiento es un campo reservado para hombres, ocasionando en algunos casos el miedo al fracaso, a menudo influenciado por las expectativas culturales, puede ser más pronunciado en las emprendedoras, este temor puede limitar la voluntad de asumir riesgos y emprender nuevos proyectos, pero sobre todo es importante reconocer que este proceso es un círculo vicioso que ha resultado difícil de romper. (Tejeiro, Molina, & García, 2021) Las expectativas culturales relacionadas con el cuidado de la familia a menudo recaen en las mujeres, esto puede dificultar la dedicación de tiempo y energía al emprendimiento, ya que se espera que las mujeres asuman la carga del trabajo doméstico y el cuidado de los hijos, sumado a aquello la brecha salarial de género, en la que las mujeres ganan menos que los hombres por el mismo trabajo, lo cual según (Orozco, 2022) puede limitar el acceso de las emprendedoras a recursos financieros y fondos para invertir en sus negocios.…”
Section: Barreras Culturales Y Socialesunclassified